Biodiesel Production Using Ultrasonic-Assisted Heterogeneous Catalytic Process - Salamatinia, Babak (2011)
Biodiesel, a product from the transesterification of alcohol and vegetable oils or animal fats, is a greener alternative to petroleum diesel. Biodiesel production process assisted by means of ultrasonic energy has been investigated. Alkaline metal earth oxide catalysts i.e. MgO, CaO, BaO and SrO were employed to catalyze the transesterification process. Initially these catalysts were tested in conventional mixing method to find out the best catalytic activities and to serve as background data. Ultrasonic was initially introduced into the reaction as a replacement for mechanical mixing.